(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione: tre domande sulla difficile costruzione di una società pluralista. Dalla Costituente ai fatidici anni ’70 - 2. La fase applicativa delle norme costituzionali in materia di libertà religiosa: fra tentennamenti politici, violazioni della legalità costituzionale e complessità sociale - 3. La “governance” nelle relazioni tra sfera pubblica e fenomeno religioso - 4. Il “cantiere Europa”: le possibilità di una democrazia (in crisi) - 5. Conclusioni. It ought to be necessary a new Italian governance for religious freedom ABSTRACT: This work highlights, in a descriptive fashion, some of the critical aspects of the relationships between the State and religious groups in Italy. Concrete legal policy proposals are suggested, within the applicable constitutional framework, taking into account the changed social, cultural and religious context of the country.